2021
DOI: 10.3389/fimmu.2021.737427
|View full text |Cite
|
Sign up to set email alerts
|

UnAIDed Class Switching in Activated B-Cells Reveals Intrinsic Features of a Self-Cleaving IgH Locus

Abstract: Activation-induced deaminase (AID) is the major actor of immunoglobulin (Ig) gene diversification in germinal center B-cells. From its first description, it was considered as mandatory for class switch recombination (CSR), and this discovery initiated a long quest for all of the AID-interacting factors controlling its activity. The mechanisms focusing AID-mediated DNA lesions to given target sequences remain incompletely understood with regards the detailed characterization of optimal substrates in which cytid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…LSR could be induced in CLL proliferation centers in secondary lymphoid organs 1 . It has been shown that some residual CSR can occur in absence of AID 2 . This seems to result from random DNA breaks and inaccurate DSB repair as also implicated in chromosome translocations.…”
Section: • Discussionmentioning
confidence: 99%
“…LSR could be induced in CLL proliferation centers in secondary lymphoid organs 1 . It has been shown that some residual CSR can occur in absence of AID 2 . This seems to result from random DNA breaks and inaccurate DSB repair as also implicated in chromosome translocations.…”
Section: • Discussionmentioning
confidence: 99%
“…However, AID by itself is not sufficient for CSR to occur, and a large part of CSR regulation involves regulated accessibility of specific targeted regions within the IgH locus. A minimal level of CSR is even detectable in an accessible IgH locus in the absence of AID, highlighting the importance of the structure and the accessibility of S regions to recombination [ 69 ]. These data show that transcribed S regions undergo rare DNA breaks even in the absence of AID, likely due to the presence of G4s and R-loops at these regions.…”
Section: The Context Of Csr and Its Regulationmentioning
confidence: 99%
“…AID G133V has genome-wide chromatin localization defects especially in the Sµ region [ 150 ]. Of note, while CSR is principally AID-dependent (and not only G4-dependent), a recent study showed that the structure of S regions and their programmed accessibility are sufficient for preserving a basal level of CSR in AID-independent conditions [ 69 ]. Indeed, in both AID-deficient mice and AID-mutant patients, CSR junctions remain detectable at low levels upon B cell activation.…”
Section: Mutations Of Various Nuclear Factors With G4-dependencementioning
confidence: 99%
“…However, AID by itself is not sufficient for CSR to occur, and a large part of CSR regulation involves regulated accessibility of specific targeted regions within the IgH locus. A minimal level of CSR is even detectable in an accessible IgH locus in the absence of AID, highlighting the importance of the structure and the accessibility of S regions to recombination [72]. Regulated accessibility to CSR is notably (but not only) related to transcriptional regulation of the S regions targeted for CSR [73][74][75][76].…”
Section: A the Csr Machinerymentioning
confidence: 99%
“…AID G133V has genome-wide chromatin localization defects, and especially to Sµ region [159]. Of note, while CSR is principally AID-dependent (and not only G4-dependent), a recent study showed that the structure of S regions and their programmed accessibility are sufficient for preserving a basal level of CSR in AID-independent conditions [72]. Indeed, in both AID-deficient mice and AID-mutant patients, CSR junctions remain detectable at low level upon B cell activation.…”
Section: Mutations Of Various Nuclear Factors With G4-dependencementioning
confidence: 99%